The impact of Caralluma munbyana extracts on Streptococcus mutans biofilm formation - Alshehri, Turki; Alkhalifah, Israa; Alotaibi, Areeb; Alsulaiman, Alaa F.; Al Madani, Abdullah; Almutairi, Basil; Balhaddad, Abdulrahman A. (Frontiers in Dental Medicine, 2025)
Background/objectivesCaralluma plants have a wide range of anti-inflammatory and antimicrobial activities. This study aims to assess the antibacterial effect of water, methanol, and ethanol extracts of Caralluma munbyana against Streptococcus mutans biofilms.MethodsThree extracts of C. munbyana were prepared using water, methanol, and ethanol. Multiple concentrations ranging between 2.93 and 93.75 mg/ml were achieved, alongside a control group with no extract, and incubated with an overnight culture of S. mutans. In the following day, the total absorbance was measured at 595 nm. Then, the biofilms were fixed and stained with 0.5% crystal violet to measure the biofilm absorbance at 490 nm. One-way ANOVA and Tukey's post-hoc tests were applied to identify which specific concentrations differed from the control.ResultsC. munbyana methanol and ethanol extracts significantly affected the total absorbance of S. mutans (P ≤ 0.001) at 46.87 and 93.75 mg/ml. For biofilm inhibition, C. munbyana water extract was effective (P ≤ 0.001) in reducing the biofilm growth at 23.44 (1.34 ± 0.08), 46.87 (1.31 ± 0.15), and 93.75 (1.04 ± 0.07) mg/ml when compared to the control (1.58 ± 0.11). More reduction was observed among methanol and ethanol extracts, as C. munbyana methanol extract significantly (P ≤ 0.001) inhibited the S. mutans biofilm growth at 23.44 (0.99 ± 0.15), 46.87 (0.12 ± 0.02), and 93.75 (0.09 ± 0.01) mg/ml. Similarly, C. munbyana ethanol extract's biofilm inhibition was observed at the concentrations of 23.44 (0.45 ± 0.12), 46.87 (0.10 ± 0.02), and 93.75 (0.09 ± 0.04) mg/ml.ConclusionThese findings suggest that C. munbyana possesses antibacterial properties against S. mutans biofilms, particularly through its methanol and ethanol extracts.